Designing a Composite Hydraulic Cylinder Using Genetic Algorithms - Michał Stosiak; Marek Lubecki; Mykola Karpenko (Actuators)
The paper points out the growing interest in the use of composite materials for load-bearing parts, including hydraulic components. The non-negligible benefits of using composite materials in mechanical engineering are pointed out. However, applications of new materials sometimes give rise to new challenges. The strength parameters of a new structure, such as a composite cylinder for a hydraulic actuator, depend on its structure, including the number of layers and the fibre angle. This paper presents the application of a genetic algorithm to optimise the process of selecting the structure of a composite cylinder for a hydraulic actuator. The operation of the algorithm and the process of selecting global parameters (hyperparameters) are described. A block diagram of the algorithm for optimising the structure selection process is presented, and the designed structure is verified.